P THE ROLE OF INFLUENCERS IN THE SPREAD OF NEW VOCABULARY - Laeli Qadrianti; Muh. Syukri Gaffar; Nurrahma; A. Anna Fauziah; Putri Amalia; Al Mutazam (Lingue : Jurnal Bahasa, Budaya, dan Sastra, 2025)
The purpose of this study is to examine the role of influencers in the dissemination of new vocabulary through social media. This research employs a qualitative research method involving social media content analysis and literature review. The study focuses on the mechanisms of new vocabulary dissemination and its impact on social communication and the development of the Indonesian language. The findings reveal that influencers utilize social media platforms such as Instagram, TikTok, and YouTube to create engaging and relevant content. Creative content in the form of short videos, memes, or interactive stories is often used to introduce new terms. Examples of vocabulary such as "Santuy," "Asyiap," and "Mager" have gained popularity through these platforms. Social media algorithms accelerate the spread of terms by increasing the visibility of content with high interaction. Additionally, direct interactions with followers through live broadcasts or Q&A sessions strengthen the emotional connection between influencers and their audience, facilitating the adoption of new vocabulary. The impact of this phenomenon is the enrichment of colloquial language, the creation of group identity, and the strengthening of relationships within digital communities. This phenomenon has also changed perceptions of the formality of the Indonesian language, with an increasing use of non-standard terms in various contexts, including in marketing. Some companies have even started adopting new vocabulary in their branding strategies. The contribution of this study can serve as a guide for educators and policymakers to understand the dynamics of language development among the younger generation, as well as to design language learning strategies that are more relevant to the language evolving on social media.